INTERAKSI SOSIAL PADA ANAK USIA DINI DITINJAU DARI PERAN ORANG TUA SELAMA PANDEMI COVID 19 - Hanita Hanita; VERONIKA LUIS (JEA (Jurnal Edukasi AUD), 2021)
There is a Covid-19 pandemic event where the rules limit interaction between humans and other humans. This rule also has an impact on early childhood, where they currently only carry out social interactions at home. However, the government issued rules related to the procedures for social interaction by complying with the Health protocol. As a result of this event, in the end, it limits the child's stimulus related to the child's social development. Research methodology Qualitative methods. The analysis in this study is the interaction of children in terms of the role of parents during the covid-19 pandemic. The research subjects consisted of 14 children aged 3-6 years. The technique used is to distribute a questionnaire through a google form, which will be filled out by parents. The data analysis phase consists of data organization, coding and data analysis. To test the credibility of the data using the data pol- ulation technique. Research results parents who allow children to keep playing with their peers because of the awareness of the characteristics of the child. Where children will be able to form attitudes and the ability to communicate with social interaction. This is supported by providing guidance and knowledge regarding the impact of the COVID-19 virus and the procedures for Health protocols when outside the home. However, there are also parents who do not allow their children to be friends with their peers for fear of contracting the Covid-19 virus.